2017
DOI: 10.1177/0309324717723466
|View full text |Cite
|
Sign up to set email alerts
|

Distributed optical sensing in composite laminates

Abstract: An optical fiber-based full-field strain measurement technique was used to investigate delamination growth in laminated composites. An experimental setup to load the test samples under idealized modes of delamination was used to investigate the ability to capture the shape and location of the delamination front. It is envisioned that the demonstrated approach has significant field applications in controlled laboratory settings where delaminations have to be located accurately. Furthermore, the ability of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…13 However, other studies have shown that embedded optical fibers do not significantly impact properties such as mode II fracture toughness. 14 The embedding of fiber optic sensors allows monitoring of in-plane strains at selected locations and depths within a composite laminate. Embedded optical fibers can be used to monitor the degree of cure during processing, and if left intact, quasi-static events and transient events through the structure's service life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, other studies have shown that embedded optical fibers do not significantly impact properties such as mode II fracture toughness. 14 The embedding of fiber optic sensors allows monitoring of in-plane strains at selected locations and depths within a composite laminate. Embedded optical fibers can be used to monitor the degree of cure during processing, and if left intact, quasi-static events and transient events through the structure's service life.…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that very low strains measured along the length of the 0 fiber direction were obtained in the unidirectional laminate, whereas most of the residual strains developed during cure were in the transverse direction and were spatially uniform, although researchers 16 have also determined that the residual strain is nearly 40% higher near the edge of the laminate and is primarily initiated by the resin-infusion process. Also, optical fibers have been widely used for damage detection [17][18][19][20] and monitoring crack growth 14,21 for structural health monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Near the ends of each bonded region, spikes occur (Points D, G) that may be associated with the overlapped regions of the optical fiber. During bonding of the optical fiber, the transverse regions (1)(2)(3)(4)(5)(6)(7)(8) were placed underneath the longitudinal fibers (A-H). This developed a distortion, or change in the radius, of the optical fiber at the ingress and egress of the bonded region as shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…laminates. Meadows et al [7] used a looping configuration to estimate the shape of the crack front generated from end-notch flexural tests. A variety of configurations are being used to detect damage and determine residual stresses.…”
Section: Analytical Approachmentioning
confidence: 99%
“…In this study, an optical fiber (OF)-based strain measurement technique was tested on laminated composites to estimate the damage area. Previous studies using embedded OFs have been used to determine delamination growth 12,13 and the strain distributions in composite bonded joints 14 and in composite repair patches. 15 Most studies using OFs use fiber Bragg grating sensors for delamination detection and location in composites [16][17][18] and metals.…”
Section: Introductionmentioning
confidence: 99%